Nickel–multiwalled carbon nanotube composite coating on aluminum alloy rotor for textile industries. (February 2016) - Selvakumar, A; Perumalraj, R; Sudagar, J; Mohan, S
Nickel-based multiwalled carbon nanotube (Ni–MWCNT) composite coatings were electrodeposited over the inner groove of an aluminim alloy rotor with Zn–Ni interlayer. The surface of the composite coating was investigated by X-ray diffraction and scanning electron microscopy. The hardness of the coating was determined by Vicker's method. It was revealed that Ni–MWCNT composite coating has uniformity in thickness over the surface of the aluminim groove and also better particle distribution over the area. It was found that there was a significant improvement in the microhardness values of Ni–MWCNT composite coating than uncoated aluminum alloy rotor. In addition, the wear resistance of the composite coated increased nine times than the uncoated substrate. Thus, Ni–MWCNT composite coated aluminum alloy rotor can enhance the performance and life-time of the rotor in the textile industries.